2018
DOI: 10.1080/10717544.2018.1458922
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic evaluation of quetiapine fumarate controlled release hybrid hydrogel: a healthier treatment of schizophrenia

Abstract: The current study aimed to rationally develop and characterize pH-sensitive controlled release hydrogels by graft polymerization of gelatin (Gel) and hydroxypropyl methyl cellulose (HPMC) in the presence of glutaraldehyde (GA) using quetiapine fumarate for the treatment of schizophrenia. The prepared hydrogels discs were subjected to various physicochemical studies including: swelling, diffusion, porosity, sol-gel analysis, Fourier transform infrared spectroscopy, differential scanning calorimetry, and scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…QF is an antipsychotic drug for treating schizophrenia and the chemical structure is shown in Figure . QF is administered twice a day and the problem of patients skipping doses has been reported in most cases . Hence, the need for a delivery system for QF that could offers extended release (ER), minimize side effects due to over‐dosage with improve compliance in schizophrenia patients and in which QF does not have any chemical interactions with the hydrogel matrix.…”
Section: Resultsmentioning
confidence: 99%
“…QF is an antipsychotic drug for treating schizophrenia and the chemical structure is shown in Figure . QF is administered twice a day and the problem of patients skipping doses has been reported in most cases . Hence, the need for a delivery system for QF that could offers extended release (ER), minimize side effects due to over‐dosage with improve compliance in schizophrenia patients and in which QF does not have any chemical interactions with the hydrogel matrix.…”
Section: Resultsmentioning
confidence: 99%
“…After taking results of all the samples, it was observed that by increasing the concentration of the PVA, the % gel fraction was increased and vice versa [41]. By increasing the polymer 'gelatin' concentration, there can be occur an increase in the % gel fraction and decrease in the sol fraction [28]. Adding or increasing concentration of glutaraldehyde in the formulations may also results in increasing of the % gel fraction, because cross-linker will cause increase entanglement of the more polymer chains of the gel formulation [42].…”
Section: Discussionmentioning
confidence: 99%
“…ANOVA and t-test were also applied. P-values occurred less than 0.01 of a result were considered of significant difference [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations